The Difference Effect of Recovery in Warm Water and Aroma Therapy Sauna Recovery against Decreased Lactic Acid Levels after Submaximal Physical Activity - Ardo Yulpiko Putra; Hari Setijono; Edy Mintarto (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Recovery is one way to reduce levels of blood lactic acid after exercising. There are several types of recovery, namely warm water recovery and aroma therapy sauna recovery. However, both types are not very well-known. This study aims to look at the differences in the effect of warm water recovery and aroma therapy sauna recovery on decreasing blood lactic acid levels after submaximal physical activity. The study design used is the randomized pre-test and post-test group design. This study used 18 people per group consisted of men aged 19 to 21 years. Subjects were divided into 2 groups K1 and K2; K1 is warm water recovery group and K2 is aroma therapy sauna recovery group. Both groups were given maximal 85% heart rate of submaximal physical activity treatment. The submaximal form of physical activity is using ergo cycle. The warm water recovery and aroma therapy sauna recovery were done after the submaximal physical activity. The warm water recovery is in the form of soaking in warm water and the aroma therapy sauna recovery is in the form of only staying silent and still in the sauna for 5 minutes long. The data obtained from the results of the study were processed using the SPSS 20 program statistics. The results showed that the mean of blood lactic acid level in the pre-test was 9.36 ± 1.82 mMol / L, the K1 group post test1 was 3.75 ± 1.04 mMol / L, group K1 post test2 2.70 ± 0.88 mMol / L, group K2 post test1 5.28 ± 1.35 mMol, L, group K2 post test2 3.12 ± 1.01 mMol / L. Data were processed using descriptive and inferential statistics (normality test, homogeneity test, paired t and free t-test) with a significance level of p <0.05. Paired t-test results showed a significant decrease in lactic acid (0,000) and free T active delta 1 and delta 1 passive p = 0.031, delta 3 active and delta 3 passive p = 0.015 which means there is a significant difference between the warm water recovery group and the aroma therapy sauna recovery group. Thus from the results of this study it can be concluded that the decrease in blood lactic acid levels is greater in the warm water type of recovery compared to the aroma therapy sauna type of recovery.